Three minutes to doomsday : an agent, a traitor, and the worst espionage breach in US history - Navarro, Joe, 1953- (Scribner, 2017)
This edge-of-your-seat memoir from former FBI agent Joe Navarro reveals the shocking, inside details of how he spearheaded a 1980s investigation into a colossal espionage breach that would have left the US defenseless in a Soviet attack.